2013
DOI: 10.1007/s10329-013-0351-9
|View full text |Cite
|
Sign up to set email alerts
|

Activity budget, diet, and use of space by two groups of squirrel monkeys (Saimiri sciureus) in eastern Amazonia

Abstract: Squirrel monkeys (Saimiri spp.) are widely distributed in the Amazon basin. This study describes the ecological and behavioral patterns of two social groups of S. sciureus in forests adjacent to the Tucuruí hydroelectric reservoir in eastern Amazonia, including range size, activity budgets, and composition of the diet. The groups were monitored at Base 4 (group B4) and Germoplasma Island (group GI). Quantitative behavioral data were collected using instantaneous scan sampling to record behavior, substrate use,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Squirrel monkeys at TBS are classified as S. sciureus macrodon , one of 10 primate species known to inhabit the site (Marsh, ). Squirrel monkeys were often observed in large groups estimated to be between 30 and 50 individuals, which is consistent with what has been documented for groups living in continuous forests (Pinheiro, Ferrari, & Lopes, ), and for the groups at TBS (Montague, Disotell, & Di Fiore, ). Data on adults and juveniles were collected; no infants were observed.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Squirrel monkeys at TBS are classified as S. sciureus macrodon , one of 10 primate species known to inhabit the site (Marsh, ). Squirrel monkeys were often observed in large groups estimated to be between 30 and 50 individuals, which is consistent with what has been documented for groups living in continuous forests (Pinheiro, Ferrari, & Lopes, ), and for the groups at TBS (Montague, Disotell, & Di Fiore, ). Data on adults and juveniles were collected; no infants were observed.…”
Section: Methodssupporting
confidence: 86%
“…Adult squirrel monkeys range in size from 622 to 779 g (Smith & Jungers, ). Squirrel monkeys were used as the model taxon because they are arboreal quadrupeds that utilize the lower to middle forest strata (Fleagle & Mittermeier, ; Fleagle, Mittermeier, & Skopec, ; Marsh, ; Mittermeier & van Roosmalen, ; Pinheiro et al, ), making them an opportune species for filming in the wild. In addition, Saimiri species have been popular model taxa in laboratory gait studies making it ideal for us to compare our results to relevant laboratory results (Miller et al, ; Schmidt, ; Shapiro et al, ; Young, ; Young, ; Vilensky & Patrick, ).…”
Section: Methodsmentioning
confidence: 99%
“…Similar signatures can also be found for ancestral Cebinae with "fertilisation" forming the top ranked individual BP GO term, as well as more broadly on motile cilia. In line with the shift to multimale multi-female mating systems, cebid lineages are also characterised by larger group sizes, which is particularly notable for squirrel monkeys (68), and may underlie some of the enriched immune system related results recovered for ancestral Cebidae, squirrel monkeys, and ancestral Cebinae.…”
Section: Reproduction and Mating Systemsmentioning
confidence: 89%
“…18 These animals are insectivores and frugivores, and their food includes arthropods, mollusks, small vertebrates, fruits, and seeds. 19 Squirrel monkeys are among the most used neotropical primates in biomedical research, with the first studies reported by Klu¨ver, 20 who provided information on their experimental use and management in captivity. Because of their small size (with a body mass of approximately 1 kg), squirrel monkeys can be kept in smaller spaces than necessary for other model NHPs.…”
Section: Use Of Saimiri Sp In Human Obstetrical Researchmentioning
confidence: 99%